If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 * 10 + 10y = 80 Multiply 8 * 10 80 + 10y = 80 Add '-80' to each side of the equation. 80 + -80 + 10y = 80 + -80 Combine like terms: 80 + -80 = 0 0 + 10y = 80 + -80 10y = 80 + -80 Combine like terms: 80 + -80 = 0 10y = 0 Solving 10y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '10'. y = 0 Simplifying y = 0
| =2(3b+5)+4(2b-3) | | 4x^2+5k=(5k+1)x | | 13x-49=7x+29 | | =3(a+2b)-3b | | 2+cosx=0 | | 2+2cosx=0 | | x^2=18y^2-y^4 | | 8ab+12ab-12a= | | 7(h+1)=3+7h | | 3(g-1)=-2(2+g) | | 36x^2y^3+xy^2= | | =b(b+3)-2 | | =6(a+3)+2 | | =8a+2(5-b)-2a | | 6x^3+4x^2-14x+4=0 | | 125r^2-45= | | 3(2d+3)=12 | | 12r^2-75= | | =13a-b+3-6a+b | | 18.50+d=26.5 | | =7+a(3+b)-2 | | (49x^2-14x+1)(49x^2-15x+1)=0 | | =3+6(8+b)+2(b+b) | | =3a-4+2b-a+11 | | 15x^2+2xy-8y^2= | | 8.5+1m= | | =4a*3a | | =4*a-2(3*a-5) | | =4a-2(3a-5) | | 25b^2-195b-40= | | log(3)m=2-log(3)n | | 8x+7=9x+2 |